Review of the Fund's Transparency Policy. (Policy Papers; Policy Paper, 2005)
This review analyzes trends in publication of IMF documents and experience with various aspects of the transparency policy since July 2003, based on: Fund-wide data on publication; records of changes made to published staff reports; a survey of mission chiefs; and ten country case studies involving interviews with staff and Executive Directors.